Evaluation of different observation methods of the unknown points using three points resection - A. Alkanaani, Hayder (International Journal of Engineering and Technology, 2019)
In the current times, landscape works in general, and locating points in particular, depend on modern software and survey techniques, since they adopt AI (artificial intelligence) in calculations, thus the results are better if compared to manual calculations which have errors and mistakes. Here, the need to invent methods to check the accuracy of results has emerged, in order to reduces mistakes and errors. Additionally, these methods are adopted to find the unknown coor-dinates or check the calculated coordinates for those points using different methods, whether they were traditional or use the modern survey devices.The process of calculating the coordinates with the use of engineering drawing featured by the dependence on pixels when they locate any point on the drawing screen, so, it is a very accurate method compared to visual devices and manual calculations. And depending on the above concept, the research depended three known points, and the unknown location of a point was found through these points using (Resection) method. The point was located in three different locations and its position was calculated using four different methods (manual cadastral computations, modern devices, engineering drawing software and websites). The results obtained from the three methods were compared in the end of the research, the comparison showed that the use of (manual cadastral computations), which depends the accuracy of 3 ranks after comma (millimeters) in calculations and for distance of approximately half kilometer between the known points and the unknown point, caused various errors among the four methods, while the methods that depend on software and websites gave a great match in their coordinates. The reason behind that was excluding the distance calculation as in manual and instruments methods. It was shown that distance and distribution of points play an important role in locating the unknown point accurately. Also itâ€™s shown that the use of devices and manual calculations are not proportional for finding precise results, where one of them was better than the other if right steps are followed.Â Â